Reality Play. - Woodward, Richard B. (American Prospect, 2006)
A review of director Steven Soderbergh's new film, Bubble, is presented. In this film, Soderbergh moves away from such slick Hollywood fare as Ocean's Eleven and Ocean's Twelve to take a cynical and realistic look at the crisis of rustbelt America. Shot for just $1.6 million in several towns along the Ohio–West Virginia border, the film focuses on the working poor who have little or no prospect of self-improvement.